Enfermedades crónicas en personas con discapacidad y su relación con la funcionalidad familiar, Loja 2016. - Conde Minga, Esther Paola (2017)
Nowadays, there are few studies about the true health situation of people with disabilities, much less focused on their family environment; this is why the need arises to carry out the present research whose objective was to establish the relationship between chronic diseases and the family functionality of people with severe and very severe disability in the Province of Loja. The research topic was part of a Macro Project titled: "People with disabilities and their problems in the province of Loja in 2016," which was made up of five students of the Specialization in Family and Community Medicine. It was a quantitative, descriptive, correlational, analytical cross-sectional study with a sample of 397 people with severe and very severe disability residing in 13 cantons of the province of Loja. In order to measure the different variables, the family APGAR was used to assess the degree of family functionality and a semi-structured survey in which the diagnosed chronic diseases presented by the study population, which included questions from the Morisky Green adherence test, were investigated. The data extracted were analyzed by the statistical program SPSS Version 16, which demonstrated a statistically significant association between the variables chronic diseases and family functionality of people with disabilities; Obtaining a prevalence of 52.64% of these diseases in our locality. In addition, it was evidenced that the greater the family dysfunction, the greater the risk of non-compliance. All these results created a basis for the development of more studies and practical applications that can be implemented in the Ministry of Public Health and Ministry of Economic and Social Inclusion with greater awareness in addressing the care of people with disabilities. Key words: Non-communicable diseases, disability, dysfunction, therapeutic adherence, Family Apgar.